Chemical constituents of palm wastes slow pyrolysis derived vinegar - Ebrahimi, Ghanbar; Shakeri, Alireza; Ahmadi, Pyman; Dalvand, Mosayeb; Shafee, Masoud; Hosseinabadi, Hamid Zare (Maderas. Ciencia y Tecnología, 2022)
Out of rachis and stem of palm tree from grooves in humid and dry zones, test materials were randomly collected and chipped for slow pyrolysis process. Chemical constituents of a set of pyrolysis derived vinegar were identified in their aqueous phase by gas chromatograph and quantitatively compared in sampled parts of sampled tree and grooves. Another set of vinegar was dewatered by dichloromethane, then their constituents were identified by gas chromatograph coupled with mass spectrometer, chemical constituents in aqueous state in both sampled grooves were the same but with different percentage values. In the organic phase, common chemical constituents of sampled parts and grooves were quantitatively compared. In humid zone rachis was 2,22 times richer in acetic acid and 2,37 times in phenol, but in dry zone stem is richer in acetic acid by 15,35 %. In their organic phases dominant and comparable chemicals of stem and rachis from sampled zone were furfural, phenol, benzic acid, 5-methyl-2- furancarboraldehyde, butanic acid and 2-methyl-phenol. Stem from dry zone was richer in these chemicals by 36,55 %, 96,93 %, 6,37 times, 62,05, 49, 32,57 % respectively. Rachis of humid zone contained more furfural, 63,95 %, 22,08 %, 2-methyl-phenol, but that of dry zone was richer in phenol by 46,20 %, 2,5 times in benzoic acid. Results from both phases of vinegar indicate that ecological impacts on the chemical constituents of palm from the same species are evident.